Iodinated Contrast Media and the Alleged “Iodine Allergy”: An Inexact Diagnosis Leading to Inferior Radiologic Management and Adverse Drug Reactions - Böhm, Ingrid; Nairz, Knud; Morelli, John N.; Keller, Patricia Silva Hasembank; Heverhagen, Johannes T. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2017)
Purpose To test the hypothesis that the incomplete diagnosis “iodine allergy” is a possibly dangerous concept for patients under routine radiologic conditions.Materials and Methods 300 patients with a history of an “iodine allergy“ were retrospectively screened and compared with two age-, sex-, and procedure-matched groups of patients either diagnosed with a nonspecific “iodine contrast medium (ICM) allergy” or an allergy to a specific ICM agent. For all groups, the clinical symptoms of the most recent past adverse drug reaction (ADR), prophylactic actions taken for subsequent imaging, and ultimate outcome were recorded and analyzed.Results The diagnosis “iodine allergy“ was not otherwise specified in 84.3 % patients. For this group, in most cases, the symptoms of the previous ADRs were not documented. In contrast, the type of ADR was undocumented in only a minority of patients in the comparison groups. In the group of patients with an “iodine allergy” the percentage of unenhanced CT scans was greater than within the other two groups (36.7 % vs. 28.7 %/18.6 %). ADRs following prophylactic measures were only observed in the “iodine allergy” group (OR of 9.24 95 % CI 1.16 – 73.45; p < 0.04).Conclusion This data confirms the hypothesis that the diagnosis “iodine allergy” is potentially dangerous and results in uncertainty in clinical management and sometimes even ineffective prophylactic measures.Key points Citation Format
Keywords: CT; contrast agents; drugs/reactions; safety